2019
DOI: 10.1194/jlr.p094763
|View full text |Cite
|
Sign up to set email alerts
|

Potent reduction of plasma lipoprotein (a) with an antisense oligonucleotide in human subjects does not affect ex vivo fibrinolysis

Abstract: It is postulated that lipoprotein (a) [Lp(a)] inhibits fibrinolysis, but this hypothesis has not been tested in humans due to the lack of specific Lp(a) lowering agents. Patients with elevated Lp(a) were randomized to antisense oligonucleotide [IONIS-APO(a) Rx ] directed to apo(a) (n = 7) or placebo (n = 10). Ex vivo plasma lysis times and antigen concentrations of plasminogen, factor XI, plasminogen activator inhibitor 1, thrombin activatable fibrinolysis inhibitor, and fibrinogen at baseline, day 85/92/99 (p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(25 citation statements)
references
References 41 publications
(59 reference statements)
1
24
0
Order By: Relevance
“…Results of flow cytometry analyzing surface protein expression on platelets confirmed these results. These findings, along with similar data from coagulation studies [26] showing no effect on fibrinolysis parameters with potent Lp(a) lowering treatment, suggest that the risk for coronary vascular disease associated with levels of Lp(a) may be primarily mediated by pro-atherogenic and pro-inflammatory effects via its oxidized phospholipids rather [27] than by anti-fibrinolytic or anti-platelet effects. These findings may have implications in the mechanism of any potential benefit in an ongoing trial testing the "Lp(a) hypothesis" with Lp(a) lowering by an antisense oligonucleotide (ClinicalTrials.gov Identifier: NCT04023552).…”
Section: Discussionsupporting
confidence: 62%
“…Results of flow cytometry analyzing surface protein expression on platelets confirmed these results. These findings, along with similar data from coagulation studies [26] showing no effect on fibrinolysis parameters with potent Lp(a) lowering treatment, suggest that the risk for coronary vascular disease associated with levels of Lp(a) may be primarily mediated by pro-atherogenic and pro-inflammatory effects via its oxidized phospholipids rather [27] than by anti-fibrinolytic or anti-platelet effects. These findings may have implications in the mechanism of any potential benefit in an ongoing trial testing the "Lp(a) hypothesis" with Lp(a) lowering by an antisense oligonucleotide (ClinicalTrials.gov Identifier: NCT04023552).…”
Section: Discussionsupporting
confidence: 62%
“…The pro-thrombotic effect of Lp(a) in clinical studies has been controversial, with substantiation in some observational studies with a preponderance of elevated Lp(a) levels in VTE patients compared with controls (Lp[a] elevation in 20% of VTE patients compared with 7% in controls; 95% 1.9–5.3, p < 0.001) [ 18 ]. However, genetic studies [ 19 ] and in vitro studies failed to support a causal role [ 20 ]. Lp(a) concentrations in the biobank were also not associated with thromboembolic events in COVID-19 patients [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, the underlying mechanism for such interaction effect between Lp (a) and fibrinogen level is not clear. In fact, a recent study has demonstrated that reduction in Lp(a) by antisense oligonucleotide in patients with very high Lp(a) levels does not affect the ex vivo fibrinolysis [53]. Further studies are therefore needed to assess whether Lp(a) interacts with IL-2 sRα, sTNF-R1 and fibrinogen in the association with clinical CVD outcome events.…”
Section: Discussionmentioning
confidence: 99%